Effect of Compensation and Internal Control Perceived Behavioral Control Behavior Of Fraud - MINANARI, Minanari (International Journal of Environmental, Sustainability, and Social Science, 2021)
The purpose of this study was to examine the effect of compensation suitability, effectiveness of the internal control system, and perceived behavioral control on fraudulent behavior in the State Civil Apparatus (ASN) in Tangerang City Government. The Data of this study were Obtained from the questionnaire answers (primary). The research findings show that the compensation suitability, effectiveness of internal control partially has a negative and significant effect on the behavior of the State Civil Service (ASN) fraud in Tangerang City Government and perceived behavioral control partially has a positive and significant effect on the behavior of State Civil Apparatus (ASN) fraud the environment of the City Government of Tangerang City. This research concludes that: (1) the more Appropriate the compensation,